Experiment and Model Investigation on the Permeability Evolution of Granite under Triaxial Compressive Damage - Zhenxing Ji; Zhide Wu; Hong Yang; Lihua Zhang; Zhenhua Ouyang; Haiyang Yi (Geofluids)
Deep granite is the ideal surrounding rock for nuclear waste geological disposal reservoir and its permeability is the key factor for nuclide migration. In order to study the permeability evolution characteristics of surrounding rocks in the near field of the disposal reservoir under different confining pressures during excavation, the mechanical and permeability properties of granite were explored through triaxial compression experiments associated with acoustic emission techniques. Experiment results suggest that the permeability exhibited typical pore percolation and fracture flow during the compressive damage process and it has an obvious relationship with the volumetric strain before and after dilation. According to such a relationship, a full-stage permeability model was proposed which is characterized by only 2 parameters. This permeability model was verified by the experiment data to be of good feasibility and effectiveness, exhibiting well fitness to the experiment under various confining pressures. According to the elastoplastic mechanical model that is available from other researchers, discussion was implemented and which convinced us that it is feasible to reproduce the real conditions of hydromechanical processes by combing the proposed permeability model and damage-based elastoplastic model in numerical modelling.